1989
DOI: 10.1128/jvi.63.3.1485-1488.1989
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of membrane antigens on human cytomegalovirus-infected fibroblasts recognized by human antibodies

Abstract: The antigens on the surface of human cytomegalovirus (HCMV)-infected fibroblasts which are recognized by human HCMV antibody-positive sera were characterized. Three HCMV-induced polypeptides, with apparent molecular masses of 53 to 63, 94, and 94 to 120 kilodaltons, were precipitated from '251-surface-labeled cell extracts with different sera obtained from healthy individuals. Renal transplant recipients who were suffering from active HCMV infections recognized the same set of antigens. By the use of monoclona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The detection of gp55 on the surface of infected cells was anticipated because previous studies utilizing monoclonal anti-gp55 antibodies have shown that these antibodies reacted with the surface of infected cells (35). However, the finding of gpll6 and gp170 on the cell surface was somewhat unexpected.…”
Section: Discussionmentioning
confidence: 98%
“…The detection of gp55 on the surface of infected cells was anticipated because previous studies utilizing monoclonal anti-gp55 antibodies have shown that these antibodies reacted with the surface of infected cells (35). However, the finding of gpll6 and gp170 on the cell surface was somewhat unexpected.…”
Section: Discussionmentioning
confidence: 98%
“…In this investigation, the immune response to CMV gB at the clonal level is extended from the immunized mouse system to the naturally infected human host. Previously, data on the reactivity of human polyclonal antibodies against the gB antigen have been collected (3,5,19,22,26,38,48), and it has been shown that 40 to 70% of serum CMV-neutralizing activity is specific for gB (4). Three to seven epitopes have been described for the major neutralizing determinant of gp58, on the basis of studies of the murine immune response against gB (20,29,37).…”
Section: Discussionmentioning
confidence: 99%